2008
DOI: 10.1208/s12249-008-9050-z
|View full text |Cite
|
Sign up to set email alerts
|

Solubility Improvement of Drugs using N-Methyl Pyrrolidone

Abstract: Abstract. The solubilization efficiency of N-methyl pyrrolidone (NMP) has been determined and compared to that of ethanol and propylene glycol for 13 poorly soluble drugs. NMP is found to be a more efficient solubilizer for all the drugs studied. The solubility enhancement as high as about 800-fold is obtained in 20% v/v NMP solution as compared to water. The mechanism of drug solubilization by NMP has also been investigated. It is proposed that NMP enhances drug solubility by simultaneously acting as a cosolv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
64
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(75 citation statements)
references
References 18 publications
(22 reference statements)
1
64
0
2
Order By: Relevance
“…We chose NMP for exploring this potential application due to its thermal stability and low toxicity. Furthermore, it had been demonstrated that NMP had a greater solubilizing power than ethanol and propylene glycol, 11 and NMP was previously used for solubility enhancements both in bioassays 31 and commercial pharmaceutical applications such as the Eligard Ò formulation for delivery of leuprolide to prostate cancer patients. We stored the compound test set (Fig.…”
Section: Properties Of 3/nmp Solutionsmentioning
confidence: 99%
“…We chose NMP for exploring this potential application due to its thermal stability and low toxicity. Furthermore, it had been demonstrated that NMP had a greater solubilizing power than ethanol and propylene glycol, 11 and NMP was previously used for solubility enhancements both in bioassays 31 and commercial pharmaceutical applications such as the Eligard Ò formulation for delivery of leuprolide to prostate cancer patients. We stored the compound test set (Fig.…”
Section: Properties Of 3/nmp Solutionsmentioning
confidence: 99%
“…For example, in a previous study, it was demonstrated that the solubilizing effect of NMP for estrone and griseofulvine drugs showed a positive deviation of linearity from the log-linear model, as a consequence of the dual mechanism whereby NMP modified drug solubility (co-solvency and complexing) (Sanghvi et al, 2008). In this present study, deviations of linearity were not identified, corroborating the idea that the solubilizing effect of the TEA and NMP for the TRI drug occurred through the co-solvency mechanism.…”
Section: Phase Solubility Studiesmentioning
confidence: 99%
“…Thus, deviations from linearity could be noticed when the solubilizing compounds modify these interactions, for example, when the solubilization ionizes the drug or forms a complex, modifying its initial structure and interaction mechanisms with the aqueous medium (Sanghvi et al, 2008).…”
Section: Phase Solubility Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Solubility of MLX in Solutol HS 15, Transcutol P and Tween 80 was 9.5, 5.4 and 5.0 mg mL -1 , respectively. NMP was selected as the vehicle of choice to formulate MLX gel, based on its solubilization capacity and penetration enhancing effect on hydrophilic and hydrophobic actives as well as dermal acceptability (17,18).…”
Section: Solubilitymentioning
confidence: 99%